COST programa – puiki patirtis jauniesiems mokslininkams - Simona Lavinskienė (Pulmonologija ir alergologija, 2014)
COST is an intergovernmental framework for European Cooperation in Science and Technology, allowing the coordination of nationally-funded research on a European level. Short Term Scientific Missions (STSMs) are travel grants aimed at strengthening the existing COST action network by allowing scientists to go to an institution or laboratory in another COST member state. STSM is the important step in the collaborative project „Eosinophil induced airway smooth muscle remodelling in asthma“ between Lithuanian University of Health Sciences and Groningen University. It confirms that COST Actions are the great opportunity for young scientists to gain invaluable experience in host institutions for the development scientific ideas and furure collaborations.